Пух, летающая собака - Одинцова Людмила (Лапы, крылья и хвосты, 2011)
Экземпляры: Селтинская детская библиотека (20120423) / Инвентарный номер: 198866 / Цена: 183.38 / Авт.знак: О-42 / ГРНТИ: 17.82 / ББК: 84(2=411.2)6